Evaluate the difference quotient for the given function. Simplify your answer.
f(x) = 5 + 4x – x2,
f(3 + h) – f(3)
h
1-1-2h-h² x
Enhanced Feedback
Please try again. To evaluate f(a + h), replace x by (a + h) in the expression for f(x). Substitute this
Need Help?
Read It
Watch It
Show My Work (Required)
What steps or reasoning did you use? Your work counts towards your score.
substituting (3+h) into the equation by replacing (3+h) where there is a x value we can get the quotient. Then repla

Respuesta :

Answer:

  -2-h

Step-by-step explanation:

It doesn't hurt to follow directions.

  [tex]q=\dfrac{f(3+h)-f(3)}{h}=\dfrac{(5 +4(3+h)-(3+h)^2)-(5 +4(3)-(3)^2)}{h}\\\\=\dfrac{5-5+4(3+h-3)-((3+h)^2-3^2)}{h}=\dfrac{4h-(6h+h^2)}{h}\\\\=\dfrac{-2h-h^2}{h}=\boxed{-2-h}[/tex]

__

Steps: substitute 3+h and 3 for x in the definition of f(x) and simplify the result.